Analisis doktrin akidah ahli sunnah wa al-jamaah dalam kitab perisai bagi sekalian mukallaf atau simpulan iman atas mazhab salaf karya Syeikh ‘Abd Al-Qādir Al-MandilῙ - Muhammad Ihsan, Idris (2022)
The Salaf belief has become the main framework for forming the members of the Sunnah wa al-Jamaah school of thought long before the emergence of the Khalaf belief. Sheikh 'Abd. Al-Qadir al-Mandili, through his work Perisai Bagi Sekalian Atau Simpulan Iman Atas Mazhab Salaf, was one of the earliest Malay scholars to introduce the Salaf belief to Malay Muslims in Malaysia, particularly. Based on the perception of some Muslim communities, the Salaf belief is not considered part of the movement of members of Sunnah. When this trend is highlighted even for scholarly purposes, it is considered awkward and even results in the phenomenon of apostasy among Muslims. Thus, through this study, one of the comprehensive questions to be studied is what the position of the Salaf belief in the framework of the belief of Sunnah wa al-Jamaah members is, and to what extent the manhaj talaqqi and the al-Mandili belief in the Perisai book are parallel to the manhaj of the Salaf al-Soleh belief. The study's main objective is to identify the Salaf belief in the framework of the members of Sunnah belief, then analyse the Salaf belief in the Perisai book. This qualitative study employs the literature review method to obtain results by collecting and analysing textual data. The result proved that the Salaf belief is the foundation of the formation of the Sunnah wa al-Jamaah members. Through the Perisai book, al Mandili highlights the method of argumentation and the understanding of the Salaf belief in the debate on the Pillars of Faith. The manhaj and understanding of the belief highlighted by al-Mandili in the Perisai book are compatible with the manhaj and understanding of the Salaf al-Soleh belief. The implications of this study can serve as a catalyst for initiatives to mature society and make them more open to confronting the issue of belief comparison. More importantly, it can bridge differences and fostering greater harmony among Muslims.